2016
DOI: 10.1016/j.cognition.2016.01.015
|View full text |Cite
|
Sign up to set email alerts
|

The time course of conflict on the Cognitive Reflection Test

Abstract: Reasoning that is deliberative and reflective often requires the inhibition of intuitive responses.The Cognitive Reflection Test (CRT) is designed to assess people's ability to suppress incorrect heuristic responses in favor of deliberation. Correct responding on the CRT predicts performance on a range of tasks in which intuitive processes lead to incorrect responses, suggesting indirectly that CRT performance is related to cognitive control. Yet little is known about the cognitive processes underlying perform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
119
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 114 publications
(123 citation statements)
references
References 42 publications
4
119
0
Order By: Relevance
“…Additionally, previous studies (see Su arez-Pellicioni, N uñez-Peña, & Colom e, 2016, for a review) have shown attentional control problems in high math-anxious individuals, especially in inhibitory tasks (Stroop tasks), which could also explain the tendency to rely on salient heuristics. Indeed, several authors have noted that inhibition of the easily available heuristic response is necessary for correct performance on the CRT (e.g., B€ ockenholt, 2012;Campitelli & Gerrans, 2014;Travers et al, 2016). Morsanyi et al (2014) also explored the possibility that MA affected performance on the CRT through burdening working memory resources.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, previous studies (see Su arez-Pellicioni, N uñez-Peña, & Colom e, 2016, for a review) have shown attentional control problems in high math-anxious individuals, especially in inhibitory tasks (Stroop tasks), which could also explain the tendency to rely on salient heuristics. Indeed, several authors have noted that inhibition of the easily available heuristic response is necessary for correct performance on the CRT (e.g., B€ ockenholt, 2012;Campitelli & Gerrans, 2014;Travers et al, 2016). Morsanyi et al (2014) also explored the possibility that MA affected performance on the CRT through burdening working memory resources.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, Böckenholt (2012a) found faster response times for the intuitive response than for the correct response, indicating intuitive processes were triggered. Similarly, Travers, Rolison, and Feeney (2016) showed, through analysis of mouse cursor trajectories, that the CRT items activate intuitive processes. Other studies contradict these findings.…”
Section: Conceptualization and Operationalization Of Crmentioning
confidence: 96%
“…Others claim that incorrect responses to conflict problems, rather than being due to a failure to override the intuitive response, might arise earlier in the reasoning process and need to be attributed to an inaccurate comprehension of the problem at hand (Mata, Ferreira, Voss, & Kollei, 2017; Mata, Schubert, & Ferreira, 2014). Others address the extent of the proposal, arguing that the capacity to detect conflict might be limited to tasks where the contrast between the intuitive and the normative answers is amplified (Pennycook, Fugelsang, & Koehler, 2012) or when the underlying principle is simple (Travers, Rolison, & Feeney, 2016). These latter critiques lead to a key open question, that will be the major focus of the current studies, namely to define the boundary conditions of logical intuitions.…”
Section: Introductionmentioning
confidence: 99%